Satellite observation of medium-scale traveling ionospheric disturbances over Syowa Station - Ogawa, Tadahiko; Igarashi, Kiyoshi; Aikyou, Kazuhiro; Maeno, Hideo (National Institute of Polar Research, 1988)
P(論文) From March 9,1985 to January 11,1986,428 medium-scale traveling ionospheric disturbances (TID's) were detected at Syowa Station, Antarctica, by means of differential-Doppler measurements with the 150 and 400MHz beacon waves from six NNSS satellites. It is found from statistical analysis that (1) the medium-scale TID's in the polar regions appear quite often during geomagnetically quiet and moderately disturbed conditions and their occurrence seems not to increase with increasing geomagnetic activity, (2) they attain the maximum activity in winter and the minimum in summer, (3) diurnal variation shows the maximum occurrence around 1400-1600LT with a second maximum around midnight, and (4) most of the medium-scale TID's propagate from south toward the equator. These findings are compared with observations made at midlatitude to find a fairly good consistency between both results. It is pointed out that the gravity waves excited in the mesosphere rather than in the auroral ionosphere play an important role in producing most of the observed medium-scale TID's. departmental bulletin paper